Efeitos das ocupações não agropecuárias sobre a renda e as horas de trabalho em zonas rurais do Brasil - Cruz, Nayara Barbosa da (2018)
In the last decades, the field has won new functions, made it possible new job opportunities and higher incomes for families. The aim of this study was to estimate the effect of non-agricultural activities on income and the number of hours allocated to the labor market in rural areas. This analysis, the first chapter, covers Brazil and as Regions, uses PNAD data from 2009 and 2015. In turn, in chapter two, the labor market of the MATOPIBA Region is studied, comparing the results of the 2000 Census with that of 2010. Both observations were balanced by the Entropy method and then the Propensity Score Matching was applied. From the results found, it was verified that the rural economy is increasingly dependent on non-agricultural activities. Specifically, for Brazil and regions, the first chapter concludes that if there is a change in activity, from the agricultural sector to a non-agricultural sector, there will be an increase in the income of the workers, except for the Central-West region, which presented 27% higher income for agricultural workers in 2015 and 22% in 2009. Regarding working hours, it was concluded that more hours are devoted to agricultural activities, except in the Northeast, that the difference was 2.6 hours more for non-agricultural workers in 2015. The results for MATOPIBA, chapter two, show that in 2010 there was an evolution of 14.32% more in income, than that created by non-agricultural activities in 2000. As for the hours worked, for the first year of the analysis, it was verified that if an agricultural worker were moved to the branch of non-agricultural activities, they would tend to work 3.37 hours less. For the year 2010, the results were not statistically significant, it is concluded that there are not enough arguments to prove that the non-agricultural activities are related to the hours worked per year.